Phytochemical Profile and Pharmacological Activity of Local Velvet Bean (Mucuna pruriens) of Timor - Tefa, Azor Yulianus; Nino, Jefrianus; Ceunfin, Syprianus; Taloin, Rensani; Yani, Ahmad (Yayasan Ahmad Mansyur Nasirah, 2025)
The processing of velvet beans (Mucuna pruriens) from Timor is traditionally done by boiling them repeatedly twelve times before consumption due to concerns about their antinutrient content. On the other hand, earlier research indicated that velvet beans possess bioactive compounds that may serve as antioxidant and antidiabetic agents. The purpose of this study was to identify the bioactive components in extracts of velvet beans grown by the Timorese community, assess the overall levels of secondary metabolite compounds, and evaluate their bioactivities through in vitro antioxidant and hyperglycemia tests. Velvet beans samples were extracted using maceration, soaking them in ethanol and n-hexane solvents, followed by qualitative phytochemical analysis. Additionally, quantitative determination of secondary metabolites was performed, along with pharmacological activity tests, which included assessing antioxidant activity and antidiabetic effects through the spectrophotometric method. The findings revealed that the local Timor velvet beans extract contained flavonoid compounds at a concentration of 12.77 ± 3.10 mg QE/g, while the levels of phenolic and tannin compounds in the extract could not be quantified due to an absorbance lower than the y-intercept. The DPPH test demonstrated that the antioxidant activity of the local Timor velvet beans extract was measured at 1,964.51 ppm, which is categorized as very weak in comparison to the standard ascorbic acid solution that registered a value of 5.39, classified as very strong. The antidiabetic assessment indicated that the extract could inhibit the activity of the α-glucosidase enzyme at a concentration of 1,000 ppm by 28.60 ± 1.10%, which is categorized as very weak relative to the results from acarbose. Further investigation is necessary to optimize the bioactive compounds and identify the content of anti-nutritional compounds, as well as to explore effective methods of processing local Timor velvet beans that can reduce the antinutritional compounds.